2022
DOI: 10.1128/msphere.00506-22
|View full text |Cite
|
Sign up to set email alerts
|

Control of Human Anelloviruses by Cytosine to Uracil Genome Editing

Abstract: Despite significant attention on anellovirus research, the interaction between the anellovirus virome and the human host remains unknown. We show the dynamics of APOBEC3-mediated cytidine deaminase activity on anelloviruses during a 30-year period of chronic infection and postulate that this antiviral mechanism controls anelloviruses. These results expand our knowledge of anellovirus-host interactions, which may be important for the design of gene therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 71 publications
(103 reference statements)
0
10
0
Order By: Relevance
“…We suggest that in future research, anelloviruses should not be approached as one virus, but several. Differences between subgenera and/or isolates were detected regarding increased anellovirus load in immunosuppressed individuals (Blatter et al 2018 ), APOBEC3 susceptibility (Timmerman et al 2022 ) and antibody reactivity (Venkataraman et al 2022 ). It would be of interest to investigate whether subgenera, or isolates, are more immunogenic or tolerogenic compared to others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We suggest that in future research, anelloviruses should not be approached as one virus, but several. Differences between subgenera and/or isolates were detected regarding increased anellovirus load in immunosuppressed individuals (Blatter et al 2018 ), APOBEC3 susceptibility (Timmerman et al 2022 ) and antibody reactivity (Venkataraman et al 2022 ). It would be of interest to investigate whether subgenera, or isolates, are more immunogenic or tolerogenic compared to others.…”
Section: Discussionmentioning
confidence: 99%
“…These predictions were recently confirmed by us. By next generation sequencing, we investigated hypermutations in 64 anellovirus isolates in healthy people, and revealed that all three human anellovirus genera are affected by C to U deamination, with some isolates more vulnerable to deamination than others (Timmerman et al 2022 ). The U-containing genomes were packaged inside intact virus particles, which we know because the clinical materials were treated with DNAse prior to analysis.…”
Section: The Innate Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Since anelloviruses use a host polymerase ( 35 ), they might not exhibit high mutation rates ( 10 ), although some indirect evidence casts doubt on this assumption. On one hand, anellovirus genomes with hypermutation patterns consistent with antiviral host innate immunity exerted by APOBEC3 proteins have been described ( 36 ). However, it has been suggested that this antiviral defense mechanism does not play a major role in viral evolution but contributes to the stability of the anellome ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, anellovirus genomes with hypermutation patterns consistent with antiviral host innate immunity exerted by APOBEC3 proteins have been described ( 36 ). However, it has been suggested that this antiviral defense mechanism does not play a major role in viral evolution but contributes to the stability of the anellome ( 36 ). On the other hand, the ORF1 of anelloviruses has conserved motifs similar to Rep protein motifs, present in the Circoviridae and Geminiviridae families.…”
Section: Discussionmentioning
confidence: 99%